The complete human body : the definitive visual guide - Roberts, Alice M. (New York : DK Publishing, 2010)
'Understand the human body as never before, from the smallest components of a cell to complex body systems. Explore human anatomy in incredible detail and clarity through virtually life-size 3-D illustrations and scans. Discover how the body works, how it changes from infancy to old age, and what can go wrong and why'--Cover, P. [4]
The integrated body -- Anatomy -- How the body works -- Life cycle -- Diseases and disorders.
Includes index.
Keywords: Human body -- Pictorial works; Human anatomy -- Pictorial works; Human physiology -- Pictorial works